Clinical outcomes of totally implantable venous access port placement via the axillary vein in patients with head and neck malignancy. Issue 2 (March 2019) - Hong, Sun; Seo, Tae-Seok; Song, Myung Gyu; Seol, Hae-Young; Suh, Sang Il; Ryoo, In-Seon
Purpose: To evaluate the clinical outcomes and complications of totally implantable venous access port implantation via the axillary vein in patients with head and neck malignancy. Materials and methods: A total of 176 totally implantable venous access ports were placed via the axillary vein in 171 patients with head and neck malignancy between May 2012 and June 2015. The patients included 133 men and 38 women, and the mean age was 58.8 years (range: 19–84 years). Medical records were retrospectively reviewed. Results: This study included a total of 93, 237 totally implantable venous access port catheter-days (median 478 catheter-days, range: 13–1380 catheter-days). Of the 176 implanted totally implantable venous access port, complications developed in nine cases (5.1%), with the overall incidence of 0.097 events/1000 catheter-days. The complications were three central line-associated blood-stream infection cases, one case of keloid scar at the needling access site, and five cases of central vein stenosis or thrombosis on neck computed tomography images. The 133 cases for which neck computed tomography images were available had a total of 59, 777 totally implantable venous access port catheter-days (median 399 catheter-days, range: 38–1207 catheter-days). On neck computed tomography evaluation, the incidence of central vein stenosis or thrombosis was 0.083 events/1000 catheter-days. Thrombosis developed in four cases, yielding an incidence of 0.067 events/1000 catheter-days. All four patients presented with thrombus in the axillary or subclavian vein. Stenosis occurred in one case yielding an incidence of 0.017 events/1000 catheter-days. One case was catheter-related brachiocephalic vein stenosis, and the other case was subclavian vein stenosis due to extrinsic compression by tumor progression. Of the nine complication cases, six underwent port removal. Conclusion: These data indicate that totally implantable venous access port implantation via the axillary vein in patients with head and neck malignancy is safe and feasible, with a low axillary vein access-related complication rate.